Factors influencing parental intention on children involvement in music curriculum education - Peng, Dandan; Keat, Ooi Boon; Khatibi, Ali; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
Music education for children is vital to their holistic development. Parents are the decision-makers of their children’s involvement in music education. Therefore, research on parental intention is significant for optimizing children’s music education and promoting their physical and mental development. In this study, we chose Henan Province in China as the study area to explore the factors influencing parental intention regarding children’s involvement in music curriculum education. An extended TPB model was constructed to explain the influence of parental intention (PI) in terms of both parental aspects (Parental attitude: ATT, subjective norms: SN, perceived behavioral control: PBC, and social stratification: SS) and music education institution aspects (Quality: QUA). A sample of 650 parents from 21 music education institutions in seven cities in Henan Province was selected, and data were collected by distributing electronic questionnaires to these parents. The results of the combined data analysis showed that PBC, SN, SS, QUA, and ATT are all influencing factors of PI, with PBC being the most significant factor influencing PI. All hypotheses were supported. Based on the findings of the study, the researcher made recommendations to the relevant authorities and presented a vision for future research with a view to promoting the development of children’s music education.